1989
DOI: 10.1017/s0043174500072179
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Mobility of Chlorimuron in Alabama Soils

Abstract: Soil thin-layer chromatography and a soil solution technique were used to evaluate chlorimuron adsorption and mobility in five Alabama soils. The order of adsorption was atrazine > metribuzin > chlorimuron; mobility was chlorimuron > metribuzin > atrazine. The order of adsorption of chlorimuron in the five soils was Sumter clay > Eutaw clay > Lucedale fine sandy loam > Decatur silt loam > Dothan sandy loam, and Rfvalues were 0.63, 0.73, 0.69, 0.76, and 0.80, respectively. Chlorimuron mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…The n values of both BE and BS increased significantly afi:er the DCB treatment and nearly equal to each other. Additionally, the Krvalues of chlorimuron-ethyl obtained in this study were in che same range as che values determined for different soils reported previously (Goetz et al, 1989;Reddy et al, 1995b).…”
Section: Adsorption Isotherms Of Chlorimuron-ethyl In the Soils Beforsupporting
confidence: 87%
See 2 more Smart Citations
“…The n values of both BE and BS increased significantly afi:er the DCB treatment and nearly equal to each other. Additionally, the Krvalues of chlorimuron-ethyl obtained in this study were in che same range as che values determined for different soils reported previously (Goetz et al, 1989;Reddy et al, 1995b).…”
Section: Adsorption Isotherms Of Chlorimuron-ethyl In the Soils Beforsupporting
confidence: 87%
“…The importance of organic matter on the adsorption of chlorimuron-ethyl as well as other sulfonylurea herbicides in soil has been documented in the limited number of adsorption studies (Goetz et al, 1989;Reddy et al, 1995b;Zhang et al, 2007;Tang et al, 2009;Zanini et al, 2009). These results were mostly obtained by correlating adsorption coefficients to different soil characteristics based on a variety of soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grover (1968) found that reducing soil pH from 6.5 to 5.0 reduced the bioactivity of picloram, owing to increased binding of molecular forms by organic matter. The pH‐dependence of sorption has been reported for many acidic pesticides, including bentazone (Abernathy and Wax, 1973; Grey et al, 1996), chlorimuron (Goetz et al, 1989), chlorsulfuron (Shea, 1986; Walker et al, 1989), metsulfuron‐methyl (Walker et al, 1989), and picloram (Nearpass, 1976).…”
mentioning
confidence: 99%
“…Goetz et al (1989) evaluated chlorimuron sorption and mobility in Ultisols and Inceptisols, with sorption being inversely related to soil pH. Chlorimuron is a weak acid with a pK a of 4.2; therefore, anionic forms predominate in solution for most soils.…”
mentioning
confidence: 99%